COVID-19 pandemic: educational technology for post-hematopoietic stem cell transplant patients - Simone Martins Nascimento Piubello; Mitzy Tannia Reichembach; Leticia Pontes; Shirley Boller (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: to describe the experience of building the technology "Care for the prevention of COVID-19 in post-hematopoietic stem cell transplant patients". Methods: experience report conducted in a hematopoietic stem cell transplant outpatient clinic that supported the construction of an educational technology in the form of a booklet for the prevention of COVID-19. In May 2020, a literature review in scientific databases and guidelines of health organizations were used for its development. Results: printed booklet with information on the definition of coronavirus, hand hygiene, use of the mask by the patient and caregiver, isolation and social distancing and general hygiene care. Final Considerations: the use of technologies is characterized as a tool for educational actions therefore, nurses, patients and caregivers benefit from guidance processes for health care. The developed technology has the potential to minimize the impact and spread of SARS-CoV-2 among high-risk populations.